The neuroscience of attention attentional control and selection - Mangun, G. R. (George Ronald), 1956- (New York ; Oxford : Oxford University Press, 2012)
This text provides the reader with a solid overview of the mechanisms and models in the neuroscience of attentional control and selection from leading authorities working in humans and animals, and incorporating a array of neuroscience methods from single neuron recordings to functional brain imaging.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Attention; Selectivity (Psychology); Cognitive neuroscience; Visual perception